Pastoral care and the dying process of people living with HIV/AIDS speaking of God in a crisis - Kgosikwena, Kagiso B. (Missionalia: Southern African Journal of Mission Studies, 2001)
The emotional turmoil experienced by people living with AIDS is a challenge to pastoral care in Botswana. People diagnosed as HIV positive find that their lives are completely redefined and often face ostracism because of the social stigma attached to HIV/AIDS The works of Elizabeth Kobler-Ross which deal with the process of dying, can be helpful here. Dying people go through stages of denial, anger, isolation, bargaining, depression and acceptance. Their families, and even the whole society, also pass through these stages.
Free